2023
DOI: 10.1037/pha0000561
|View full text |Cite
|
Sign up to set email alerts
|

Using social network methodology to examine the effects of exposure to alcohol-related social media content on alcohol use: A critical review.

Abstract: Peer social influence is a robust predictor of problematic drinking among young adults and adolescents; it is typically assessed by collecting nonspecific social network information (i.e., behaviors of peers globally) or specific social network information (i.e., behaviors of named friends). Socialization happens both in-person and online through social media. Exposure to alcohol-related social media content is consistently related to alcohol consumption in cross-sectional and longitudinal studies alike. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…These approaches generally evidence short‐term effectiveness for reducing consumption (similar to other online alcohol interventions; for reviews see Moreno et al, 2016; Ridout, 2016; Steers et al, 2016; for a review and meta‐analysis see Vannucci et al, 2020). In addition, several studies have found that exposure to alcohol‐related social media content is linked to higher close friend descriptive drinking norms (Strowger & Braitman, 2022). Thus, interventionists may wish to include PNF showing the actual drinking levels and approval for drinking behaviors of specific influential social network members rather than peers or friends more generally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches generally evidence short‐term effectiveness for reducing consumption (similar to other online alcohol interventions; for reviews see Moreno et al, 2016; Ridout, 2016; Steers et al, 2016; for a review and meta‐analysis see Vannucci et al, 2020). In addition, several studies have found that exposure to alcohol‐related social media content is linked to higher close friend descriptive drinking norms (Strowger & Braitman, 2022). Thus, interventionists may wish to include PNF showing the actual drinking levels and approval for drinking behaviors of specific influential social network members rather than peers or friends more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Examining how close peers influence alcohol consumption and consequences via the alcohol-related social media content they share is important to examine given the robust evidence on how social influences from close peers affect college drinking (Borsari & Carey, 2001) and growing body of research linking exposure to alcohol-related content to alcohol outcomes (Curtis et al, 2018). However, prior research has commonly assessed exposure to alcohol-related content using global measures (e.g., descriptive norms) which do not adequately elucidate how content shared by named specific close peers (e.g., members of a social network or friend group) is linked to viewer alcohol consumption and consequences (for a review see Strowger & Braitman, 2022). As such, the current study built upon the findings of previous studies by examining how exposure to alcohol-related social media content shared by social network members was associated with participant alcohol consumption and consequences (Aim 1) and how qualities of relationships with social network members sharing this content were associated with alcohol outcomes (Aim 2).…”
Section: Discussmentioning
confidence: 99%
“…From an exposure standpoint, a photo showing a group of friends drinking alcohol may enhance norm perception in a greater way than a text post describing a social event in which drinking occurred. Compared to text content, visual content may be more engaging (Strowger & Braitman, 2022) and provide more key contextual information. Most substance use posts are in a positive context (Beullens & Schepers, 2013; Erevik et al, 2018; Rutherford et al, 2022), and users may see a social event in which others are enjoying themselves and each other as they consume alcohol, which in turn may increase perceived approval of and subsequent use (Nesi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The modality of a social media post (i.e., text vs. visual) may differentially relate to substance outcomes (Strowger & Braitman, 2022). Although text and visual exposure and postings tend to be highly correlated (Miller et al, 2014; Vanherle et al, 2022b), social media users may post more visual portrayals of alcohol content than text content on Facebook (Beullens & Schepers, 2013; Hendriks et al,2018b; Miller et al, 2014; Van Hoof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, most ARC studies use a global approach (e.g., ARC sharing of a group [norms]), rather than a social network approach (e.g., ARC sharing of specific individuals important to the participant [15]). Only three studies to date use a social network approach to examine how exposure to ARC shared by specific friends is related to drinking outcomes [30][31][32].…”
Section: Approaches To Examining Effects Of Alcohol Content On Drinkingmentioning
confidence: 99%